Search 74,326 tutors
FIND TUTORS
Ask a question
0 0

solve the equation by completing the square; x^2 + 5x -5 = 0

Tutors, please sign in to answer this question.

1 Answer

a^2 ± 2ab + b^2 = (a ± b)^2


x^2 + 5x - 5 = 0

(x^2 + 2*(5/2)x + 25/4) - 25/4 - 20/4 = 0

(x + 5/2)^2 = 45/4

x + (5/2) = ± √(45/4)

1). x + 5/2 = (3√5)/2

     x1 = [(3√5) - 5] / 2 

2). x + 5/2 = - (3√5)/2

     x2 = - [(3√5) + 5] / 2

Comments

(x^2 + 2*(5/2)x + 25/2) - 25/4 - 20/4 = 0
 
Just a note:  The "+ 25/2" should be " + 25/4" since (5/2)^2 = 25/4, but since you subtracted -25/4, I knew it was a typo.

Good solution Nataliya.